Specific decellularized extracellular matrix promotes the plasticity of human ocular surface epithelial cells - Ramos, Tiago; Parekh, Mohit; Meleady, Paula; O’Sullivan, Finbarr; Stewart, Rosalind M. K.; Kaye, Stephen B.; Hamill, Kevin; Ahmad, Sajjad (Frontiers in Medicine, 2022)
The ocular surface is composed of two phenotypically and functionally different epithelial cell types: corneal and the conjunctival epithelium. Upon injury or disease, ocular surface homeostasis is impaired resulting in migration of conjunctival epithelium on to the corneal surface. This can lead to incomplete transdifferentiation towards corneal epithelial-like cells in response to corneal basement membrane cues. We show that corneal extracellular matrix (ECM) proteins induce conjunctival epithelial cells to express corneal associated markers losing their conjunctival associated phenotype at both, mRNA and protein level. Corneal epithelial cells behave the same in the presence of conjunctival ECM proteins, expressing markers associated with conjunctival epithelium. This process of differentiation is accompanied by an intermediate step of cell de-differentiation as an up-regulation in the expression of epithelial stem cell markers is observed. In addition, analysis of ECM proteins by laminin screening assays showed that epithelial cell response is laminin-type dependent, and cells cultured on laminin-511 showed lower levels of lineage commitment. The phosphorylation and proteolysis levels of proteins mainly involved in cell growth and differentiation showed lower modifications in cells with lower lineage commitment. These observations showed that the ECM proteins may serve as tools to induce cell differentiation, which may have potential applications for the treatment of ocular surface injuries.